2019
DOI: 10.1002/hed.25937
|View full text |Cite
|
Sign up to set email alerts
|

Elevated incidence of head and neck cancer in solid organ transplant recipients

Abstract: Background Solid organ transplant recipients are known to be at an increased risk of cancer development, but research on head and neck cancer in transplant recipients has been limited and prior risk assessments may not be accurate. Methods A retrospective review using a national Veterans Administration database to query outpatient problem lists for ICD codes indicating solid organ transplant and subsequent diagnosis of head and neck cancer. Results In a study of 30 939 656 patients (37 969 solid organ transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
(134 reference statements)
0
10
0
Order By: Relevance
“…A large cohort study on solid organ transplant recipients, conducted by Mowery et al found increased risk of TC after transplantation [5]. RTRs constituted 50.5% of all participants in this study [5]. It was reported that the risk of TC was elevated both, after kidney transplantation and in patients with CKD on hemodialysis [41,42].…”
Section: Head and Neck Cancers (Hnc) Potentially Not Related To Viralmentioning
confidence: 48%
See 4 more Smart Citations
“…A large cohort study on solid organ transplant recipients, conducted by Mowery et al found increased risk of TC after transplantation [5]. RTRs constituted 50.5% of all participants in this study [5]. It was reported that the risk of TC was elevated both, after kidney transplantation and in patients with CKD on hemodialysis [41,42].…”
Section: Head and Neck Cancers (Hnc) Potentially Not Related To Viralmentioning
confidence: 48%
“…Thyroid cancer Thyroid cancer (TC) is another neoplasm that was suggested not to be related to viral infection [36]. A large cohort study on solid organ transplant recipients, conducted by Mowery et al found increased risk of TC after transplantation [5]. RTRs constituted 50.5% of all participants in this study [5].…”
Section: Head and Neck Cancers (Hnc) Potentially Not Related To Viralmentioning
confidence: 57%
See 3 more Smart Citations